2015
DOI: 10.1016/j.gca.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of dissolved organic matter draining permafrost soils

Abstract: Please cite this article as: Ward, C.P., Cory, R.M., Chemical composition of dissolved organic matter draining permafrost soils, Geochimica et Cosmochimica Acta (2015), doi: http://dx. AbstractNorthern circumpolar permafrost soils contain roughly twice the amount of carbon stored in the atmosphere today, but the majority of this soil organic carbon is perennially frozen.Climate warming in the Arctic is thawing permafrost soils and mobilizing previously frozen dissolved organic matter (DOM) from deeper soil lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(145 citation statements)
references
References 66 publications
(150 reference statements)
11
125
2
Order By: Relevance
“…The one study we identified measured greater concentrations of nitrate, ammonia, and DOC in leachates of permafrost soils compared to active-layer soils in cores collected near Barrow, Alaska (Reyes and Lougheed 2015), similar to our results. Differences in DOM optical properties between activelayer and permafrost soils collected from sites in arctic Alaska (Ward and Cory 2015) and northern Finland (Selvam et al 2017) are consistent with our observations of greater proportions of LMW DOM, a more 'microbial' FI signature, and lower DOM humification in permafrost soils. While our experiment focused on initial release upon thaw, boreal soils with high C and N content continue to release DOC and DON with multiple leaching events over long periods Hooper 2002, Kim et al 2014), suggesting that our short-term yields are conservative.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The one study we identified measured greater concentrations of nitrate, ammonia, and DOC in leachates of permafrost soils compared to active-layer soils in cores collected near Barrow, Alaska (Reyes and Lougheed 2015), similar to our results. Differences in DOM optical properties between activelayer and permafrost soils collected from sites in arctic Alaska (Ward and Cory 2015) and northern Finland (Selvam et al 2017) are consistent with our observations of greater proportions of LMW DOM, a more 'microbial' FI signature, and lower DOM humification in permafrost soils. While our experiment focused on initial release upon thaw, boreal soils with high C and N content continue to release DOC and DON with multiple leaching events over long periods Hooper 2002, Kim et al 2014), suggesting that our short-term yields are conservative.…”
Section: Discussionsupporting
confidence: 90%
“…Studies of soil leachates in circumpolar regions have focused primarily on potential DOC release from active-layer soils (Neff and Hooper 2002, Michaelson and Ping 2003, Guo et al 2007, Vonk et al 2015, O'Donnell et al 2016 and from deep Pleistocene yedoma soils (Dutta et al 2006, Drake et al 2015, Ewing et al 2015. Only a small number of studies have compared solute leachate chemistry and/or biodegradability from paired active-layer and shallow permafrost soils (Ward and Cory 2015, Reyes and Lougheed 2015, Selvam et al 2017 and those studies are limited to soils collected from a single location.…”
Section: Introductionmentioning
confidence: 99%
“…On 8 and 12 August 2016, we collected pore waters for detailed chemical analysis into sterile 60-ml amber borosilicate bottles, placed each bottle on ice in the field, froze them within 2 hr of collection and transported them to Colorado State University for analysis (described below). We feel our EEMS results are robust because (1) SUVA 254 values (<3.0 L·mg-C −1 ·m −1 ) were below the threshold where significant alterations have previously been found , (2) DOM chemical composition and aromatic characteristics are similar to previously reported values for unfrozen samples collected from the same sampling location (Imnavait watershed, Ward & Cory, 2015) and from other active layer soil horizons (low Arctic, Waldrop et al, 2010), (3) DOC concentrations are within range of groundwater samples collected the year prior from the same watershed (1,500-2,000 μM vs. 300-2,100 μM, respectively, Neilson et al, 2018) and DOC concentrations in unfrozen soil-water samples (Waldrop et al, 2010;Ward & Cory, 2015), (4) our NMR results support those found using EEMS, and (5) we observed no evidence of flocculation or production of brown particles in thawed samples, which is characteristic of abiotic particle formation and OM precipitation Giesy & Briese, 1978). More specifically, freeze-thaw dynamics may alter fluorescent DOM composition and concentration (>10%) when sample aromaticity is high (SUVA 254 > 3.5 L·mg-C −1 ·m −1 ; Fellman, D'Amore, & Hood, 2008; Pokrovsky et al, 2018), although evidence is mixed (Coble et al, 2014;Otero et al, 2007;Spencer et al, 2010).…”
Section: Pore Water Chemistriessupporting
confidence: 83%
“…The change of SUVA from 2.4 to 3.4 in hollows demonstrates a significant shift in the composition of the DOM and may have a pronounced effect upon the biogeochemical processing of DOM upon export, as has been recently shown in eastern Siberia . This contradicts the conclusion reached in recent studies of surface waters and soil leachates that the DOM leached from the permafrost soil layer has a consistently lower concentration of aromatic carbon (i.e., lower SUVA 254 values; Mann et al, 2012;Cory et al, 2013Cory et al, , 2014Abbott et al, 2014;Ward and Cory, 2015), compared to DOM draining from the active, organic surface layer. However, the majority of previous studies dealt with non-peat permafrost environment.…”
Section: Dissolved Organic Carbon Transport In Peat Soilscontrasting
confidence: 77%